2006
DOI: 10.1158/1055-9965.epi-05-0896
|View full text |Cite
|
Sign up to set email alerts
|

Common Genetic Variation at PTEN and Risk of Sporadic Breast and Prostate Cancer

Abstract: PTEN frequently shows loss of heterozygosity in breast and prostate cancers, and mutations in this gene are responsible for Cowden disease, a rare Mendelian syndrome that includes breast cancer as part of its phenotype. Thus, PTEN serves as a candidate susceptibility gene for both breast and prostate cancer risk. Whether common inherited variation (either coding or noncoding) at the PTEN locus contribute to nonfamilial, sporadic breast and prostate cancer risk is not known. In this study, we employed a linkage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 14 publications
1
22
1
Order By: Relevance
“…Targeting of Akt, directly or indirectly, inhibits cell proliferation, promotes apoptosis and/or increases sensitivity to chemotherapy (Tachiiri et al, 2000). The loss of PTEN expression has been reported in a variety of cancers (Rennie and Nelson, 1998;Marsit et al, 2005;Haiman et al, 2006). There are relatively a few studies exploring PTEN abnormalities in lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting of Akt, directly or indirectly, inhibits cell proliferation, promotes apoptosis and/or increases sensitivity to chemotherapy (Tachiiri et al, 2000). The loss of PTEN expression has been reported in a variety of cancers (Rennie and Nelson, 1998;Marsit et al, 2005;Haiman et al, 2006). There are relatively a few studies exploring PTEN abnormalities in lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together with other studies [18][19][20] , our results do not support PTEN as a colon cancer susceptibility gene.…”
Section: Recent Studies Have Shown Changes In the Ptencontrasting
confidence: 56%
“…In addition, PTEN missense and nonsense mutations occur in Cowden Disease, a hereditary cancer susceptibility syndrome involving multiple hamartomas of the gastrointestinal tract and other tissues [16,17] . To date, three published studies have examined PTEN as a potential candidate susceptibility gene for four cancer types: breast and prostate cancer [18] , meningiomas [19] , and colorectal cancer [20] . These studies found no association with PTEN genetic polymorphisms.…”
Section: Introductionmentioning
confidence: 99%
“…Ha i man et al in ves tiga ted the re la ti o of rs1903858 with bre ast and pros ta te can cer risks in the ir mul ti eth nic po pu la ti on study, and they co uld not find any re la ti ons. 33 Si milarly, Tre o lar et al re por ted that the re was no as soci a ti on bet we en SNP in PTEN and ma lig nant trans for ma ti on of en do met ri o sis for ma ti on. 34 In the sa me way, Song et al in ves ti ga ted the ge ne tic as soci a ti on bet we en rs1903858 and lary ngo car ci no ma in Chi ne se Han po pu la ti on, but they co uld not find any as so ci a ti on of the SNP with lary ngo car ci no ma in this po pu la ti on.…”
Section: Discussionmentioning
confidence: 99%